Observation of soliton and bound soliton in erbium-doped fiber lasers using single-walled carbon nanotubes mode-lockers under gamma irradiation. (January 2023) - Muhamad Apandi, N.H.; Ahmad, H.; Lokman, M.Q.; Zuikafly, S.N.F.; Yahaya, H.; Ibrahim, M.H.; Rosnan, R.M.; Ahmad, F.
Highlights: Erbium-doped fiber lasers (EDFLs) using gamma (γ) ray irradiated single-walled carbon nanotubes-poly(ethylene oxide) (SWCNT-PEO) film as a saturable absorber (SA). Using the liquid phase exfoliation method, a free-standing SWCNT-PEO film-based SA was developed. 1) The transmission and modulation depth of non-irradiated and irradiated nanotube mode lockers were studied, and it was discovered that at 50 Gy and 100 Gy irradiation, the trend increases, while at 200 Gy it decreases. 2) Non-irradiated and 200 Gy dosages of nanotube mode locker generate the soliton pulsed fibre laser. Irradiating the nanotube mode-locker with 50 Gy and 100 Gy produced bound soliton. Abstract: This study looked into the generation of soliton and bound-state soliton passively mode-locked Erbium-doped fiber lasers (EDFLs) using gamma (γ) ray irradiated single-walled carbon nanotubes-poly(ethylene oxide) (SWCNT-PEO) film as a saturable absorber (SA). Using the liquid phase exfoliation method, a free-standing SWCNT-PEO film-based SA was developed. The SWCNT-PEO film was non-irradiated before being integrated into the laser cavity, and then subjected to a series of low dose radiations of 50 Gy, 100 Gy, and 200 Gy. The non-irradiated film generated a soliton mode-locked pulsed fiber laser operating at 1560 nm, with a repetition rate of 23.8 MHz and a pulse width of 0.60 ps. Irradiated films of 50 Gy and 100 Gy produced bound-state solitons with pulse separations of 7.68 ps and 2.62 ps, respectively. A soliton mode-locked pulsed fiber laser with an operating wavelength of 1556 nm and a pulse width of 0.59 ps is produced for the 200 Gy irradiated film.